KONTRIBUSI RUANG LAKTASI PADA TEMPAT KERJA DI ERA KESETARAAN GENDER - Puspitasari, Sendy Krisna (EGALITA, 2023)
The best investment for female employees to promote breastfeeding at work is tha availability of lactation room. This research sought to explore the lactation room at work experiences from the persepective of employed women and field leaders. This research used an exploratory qualitative design with multi-perspective semi-structured interview. Snowball sampling was employed to recruit ten informants, field leaders (n=5) and employed women (=5), from Surabaya City Department of Education. Interviews were conducted between January until April 2023 to capture informants' experiences with breastfeeding in the lactation room. Thematic analysis was used to analyse data. Four key themes that described experiences of lactation room emerged which further traversed three critical maternity phase: pregnacy, maternity leave, and return to work. The prevalent themes are: 1) Knowledge about the regulation and lactation room support benefits. Most informants only knew about the regulated three months maternity leave. 2) Perceptions and experiences of breastfeeding in the lactation room. As a result, experiences in lactation room fulfil breastfeeding needs. 3) Barriers to lactation room continuation, such as the absence of a socialization about lactation room, and 4) Recommendations to increase support for lactation room in the era of gender quality at work from an individu, organizational, and national level.